"What if…it never ends?": Examining challenges in primary teachers' experience during the wholly online teaching. Issue 1 (2nd January 2021) - Wang, Zhuo; Pang, Hui; Zhou, Jia; Ma, Yubin; Wang, Zhonghou
Abstract: Since the outbreak of Covid-19, the Chinese government has issued strict policies for school operations. To meet the demands of normal school schedule while at home, teachers have been required to provide fully online classes regardless of their previous experience. Understanding and describing the authentic challenges teachers face during the wholly online learning and teaching period may not only allow stakeholders to make more informed decisions about subsequent practices, but also provide timely lessons for primary schools in other regions combating similar challenges. The present study was a phenomenological study, in which 26 Chinese primary school teachers were interviewed and provided photos that represented their typical online teaching experience. The essence of the study was " cautious adaptation, " and four themes were identified, including unpreparedness, concerns for at-risk students, constant change and diversity. Relevant issues and implications were discussed especially pertaining to technological innovation and advancement.